A revision of species of the Parmelia saxatilis complex in the Iberian Peninsula with the description of P. rojoi, a new potentially relict species. (September 2020) - Crespo, Ana; Rico, Víctor J.; Garrido, Elisa; Lumbsch, H. Thorsten; Divakar, Pradeep K.
Abstract: The species of the Parmelia saxatilis complex occurring in the Iberian Peninsula were revised. Eight species are accepted, including a new species found in southern Spain, described as P. rojoi A. Crespo, V. J. Rico & Divakar. The new species, which forms a sister-group relationship with P. saxatilis s. str., is rare in the Iberian Peninsula and is restricted to higher altitudes of northern and central Spain. Parmelia rojoi differs from P. saxatilis by generally narrower isidia and a more fragile thallus. The segregation of the new species is also supported by ITS (rDNA) and Mcm7 (MS456) phylogeny and multispecies coalescent-based approaches, including StarBEAST and BP&P. Furthermore, the divergence of P. rojoi is dated back to the Pleistocene, c . 2.13 Ma. A key to the identification of species from the P. saxatilis complex with their diagnostic features is provided. All species of the complex known from Europe are also found in the Iberian Peninsula. We hypothesize that P. rojoi is a relict species that survived the Pleistocene glaciations in refugia in Spain and has been unable to extend its distributional range in postglacial periods.